Transformasi Hukum Adat di Tengah Modernisasi: Antara Pelestarian Nilai Tradisional dan Adaptasi Global - Mega Ayu Putri Sanjaya; Muhammad Ircham Faridil Kudsi; Prasetyono, Dika Aries (Taruna Law: Journal of Law and Syariah, 2025)
Customary law is part of the culture of the Indonesian nation that lived in society long before the existence of modern law. Customary law is a norm that is embodied in the behavior of society. Speaking of customary law in the aspect of culture, customary law was born or grew from the habits of society that interact with each other, which reflects the basic values of Indonesian culture. Customary law plays an important role in maintaining local culture, especially in the function of maintaining and preserving cultural heritage. In this paper, customary law will be studied in the aspect of culture which includes three main points, namely; culture in society, the culture of several tribes in Indonesia, and customary cases in cultural phenomena. The method used in compiling this paper is based on literature studies by reviewing several standardized scientific reading sources in order to enrich insight into the correlation of customary law with aspects of culture. In this paper, it can be seen that culture in society is a way of life that is passed down from generation to generation, and is an inseparable part of people's lives. The culture of several tribes in Indonesia symbolizes the diversity of cultures that are an integral part of the order of life of Indonesian people.  As well as Customary Cases in Cultural Phenomena are interpreted as an action that leads to a form of violation of customary norms that gives rise to dynamics of social behavior in the wheel of community life, including the Gowok Tradition of the Javanese Tribe, the Kawin Tangkap Tradition in Poso, and Religious Conflict in Sumba.